Finite-time extended state observer-based area keeping and heading control for turret-moored vessels with uncertainties and unavailable velocities - Yulong Tuo; Shasha Wang; Chen Guo (International Journal of Naval Architecture and Ocean Engineering, 2022)
This paper investigates the finite-time extended state observer-based Dynamic Positioning (DP) control of turret-moored vessels with unavailable velocities and uncertainties. The control objective is to assist the mooring system of vessel in achieving area keeping and heading control. Firstly, unavailable velocities and uncertainties are estimated simultaneously by the designed finite-time Extended State Observer (ESO), where finite-time convergence and high accuracy of estimated values are guaranteed. Then, a reliability index is introduced to quantify the breakage probability of mooring lines. Based on estimated values and reliability index, a finite-time DP controller is proposed for area keeping and heading control of turret-moored vessels. The proposed controller can improve utilization efficiency of mooring system and guarantee finite-time convergence of all signals in closed-loop control system. Meanwhile, a saturation function is integrated into the controller to decrease the thrusters’ energy consumption. Finally, simulations and comparisons demonstrate the performance of finite-time ESO and DP controller.